Persepsi dan Minat Pramuka terhadap Integrasi Sustainable Development Goals dalam Kegiatan Kepramukaan - Agustiawan Agustiawan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study explores the perceptions, interests, and digital readiness of Scout members at the Penegak and Pandega levels regarding the integration of the Sustainable Development Goals (SDGs) into Scouting activities. A quantitative descriptive research design was applied using a survey method. Data were collected through an online questionnaire distributed via social media group chats consisting of active Scout members. A total of 75 respondents participated in the study. The findings reveal that the majority of respondents perceive Scouting activities as supportive of SDG achievement, particularly in the areas of quality education, health and well-being, environmental protection, and climate action. Leadership skill development and opportunities for social interaction emerged as the most influential factors determining interest in participating in Scouting activities. Although most respondents acknowledged the importance of technology in supporting Scouting programs, the current contribution of Scouting activities to improving digital competencies was perceived as moderate, indicating room for further development. Action-based activities, such as environmental initiatives and social service programs, were identified as the most preferred forms of SDG-related Scouting activities. Overall, the results highlight the strategic potential of the Scout Movement as a non-formal education platform for promoting sustainable development among youth. Strengthening the systematic and contextual integration of SDGs into Scouting programs is therefore recommended to maximize their educational and societal impact.